Islamic Educational Theology and Kokoda Tribe Traditional Healing Practices in Southwest Papua, Indonesia - Mawardi M. Wugaje; Hasbullah Hasbullah; Fardan Abdillah M; Abdullah Abdullah (Yayasan Haiah Nusratul Islam, 2026)
This study investigates Kokoda traditional healing from the perspective of Islamic educational theology by exploring the dialogue amongst tawhid, local culture, and healthcare practices. The research employed a qualitative approach using anthropological and local-studies perspectives. Data were collected through interviews, observations, and documentation involving 20 respondents. They consisted of four Kokoda traditional leaders, four Muslim religious leaders, two government health workers, two doctors, six patients, and two educated community members in Kokoda Regency. The findings reveal that traditional healing functions not only as medical treatment but also as a medium for transmitting moral education, ecological wisdom, and communal solidarity. Most Muslim leaders support healing practices integrated with Qur’anic recitations and Islamic prayers, while some respondents criticize ritual elements considered incompatible with tawhid. Medical workers acknowledge the cultural significance of traditional medicine but emphasize the need for biomedical supervision for severe illnesses. The study concludes that Kokoda healing traditions represent a contextual model of Islamic educational theology that strengthens cultural resilience, religious moderation, and indigenous healthcare awareness in Southwest Papua.